Catalog of the genus Choeromorpha Chevrolat, 1849 (Coleoptera: Cerambycidae: Lamiinae) in the Philippines with description of a new species from Luzon Island - Medina, Milton Norman D.; Villegas, Jhonnel P.; Barsevskis, Arvids; Vitali, Francesco (Zootaxa, 2023)
This work presents the first catalog of the genus Choeromorpha Chevrolat, 1849 for the Philippines. A total of five species and one subspecies have been described from different faunal regions of the country. This paper proposes a new species, Choeromorpha (s. str.) luzonensis sp. nov. from Aurora Province, Luzon Island. Choeromorpha brunneomaculata (Breuning, 1935), described from Patadalu, (actually, in Indonesia, Sumba, Island) is removed from the Philippine fauna. Choeromorpha subviolacea Heller, 1923 is recorded from Luzon (Bicol: Masbate Province) for the first time.